Physical parameters affecting the distribution of X-ray dose during hysterosalpingography - L. Kasprzyk; K. Chmaj-Wierzchowska; M.U. Jurczyk (IMR Press, 2020)
Objective: Hysterosalpingography (HSG) is based on the administration of a shading agent to the uterine cavity and fallopian tubes using a Schulze apparatus. An X-ray beam (X) is then directed at the abdominal area of the patient and diagnostic images are obtained for evaluation. The radiation beam and its mode of administration have a decisive influence on the radiation dose to which the patient is exposed. The aim of this study was to determine the physical parameters of this exposure in such a way that the dose distribution during the HSG examination was the most beneficial for the patient. Materials and Methods: Measurements to evaluate the effect of exposure parameters on the quality of radiological images obtained during HSG in slim and obese patients were made in 216 repetitions of the standard HSG test. Additional research data was obtained from measurements made in the X-ray laboratory at the Clinical Hospital. Results: The comparison of all measurements made for experimental models simulating a slim and obese patient demonstrated that the dose distribution most advantageous for the patient is obtained for pulsations of an X-ray tube for PPS = 6, regardless of the thickness of the patient. Conclusions: The image quality and size of the radiation dose received during the HSG examination depends on the individual characteristics of the patient. During the measurements performed in order to compare the exposure conditions set by the automatic exposure control (AEC) system and the resulting dose, this study demonstrated that the dose distribution most advantageous for the patients is obtained for pulsations on an X-ray tube for PPS = 6, regardless of the thickness of the patient.